Design and Construction of an ECG Simulator with Bipolar Leads Based on the Arduino Nano Microcontroller - Ibnu Riyanto; Dio Alif Pradana; Agoes Santika Hyperastuti; Inayah Lailatul (Universitas Panca Marga, 2025)
Electrocardiogram (ECG) devices require periodic testing and calibration to ensure diagnostic accuracy, especially in clinical settings where reliable patient monitoring is critical. However, commercially available ECG simulators remain relatively expensive and difficult to access in low-resource environments, creating a gap in the availability of affordable calibration tools. This study aims to design an economical and practical ECG simulator based on the Arduino Nano microcontroller using PWM pins to generate bipolar lead signals. The simulator features an LED indicator that mimics the human heartbeat and provides four operating modes: Mode I (Normal sinus rhythm) 80 BPM, Mode II (Bradycardia) 40 BPM, Mode III (Normal sinus rhythm) 120 BPM, and Mode IV (Tachycardia) 120 BPM. Testing was conducted by collecting data 10 times for each mode across Lead I, Lead II, and Lead III to verify BPM readings and PQRST waveform outputs on both ECG and patient monitor devices. The results demonstrated average accuracies of 98.70% on the ECG and 99.37% on the patient monitor, with deviations of 1.3% and 0.63%, respectively—well within the tolerance limits of the ECRI 410-20010301 standard (±5%). These findings indicate that the proposed simulator offers a reliable, low-cost alternative for internal calibration of patient monitors with bipolar leads, providing a practical and accessible solution for healthcare facilities with limited resources.